La prefectura y las subprefecturas ayacuchanas como artífices del nacionalismo ante el litigio fronterizo entre Perú y Ecuador (1910) - Miriam Encarnación-Pinedo; Carmen Cazorla-Zen (Historia Crítica)
Context/objective: The border conflict between Peru and Ecuador (1910) over the definition of their frontiers fueled the Peruvian nationalism that emerged in the nineteenth century. The trigger was a series of clashes at the Consulate and the Legate’s Office of Peru in Ecuador between March and May 1910. In the following pages, we will analyze the role of local and regional political bodies (prefectura and subprefecturas of the Andean region of Ayacucho) in the exaltation of nationalism used to collect resources and the “blood contingent” for the war. Methodology: We use discourse and documentary analysis of telegrams and memos sent from and to the prefectura and subprefecturas of Ayacucho. Originality: The role played by local authorities in constructing Peruvian nationalism has not been sufficiently addressed; however, it is of great importance since it allows us to understand the homogenizing effort of the nascent State and its multiple contradictions. Conclusions: We will note how the nationalism imposed by regional and local governments was accepted in theory. However, it was pretty diminished among citizens of all social sectors when it was needed to swell the troops.